Mechanical characterisation of a fibre reinforced oxide/oxide ceramic matrix composite. Issue 16 (December 2015) - Di Salvo, D.T.; Sackett, E.E.; Johnston, R.E.; Thompson, D.; Andrews, P.; Bache, M.R.
Abstract: Monotonic tension, fatigue and creep experiments were conducted on an oxide/oxide ceramic matrix composite over the range of temperature 20–1200 °C. The role of continuous fibre reinforcement, differential thermal expansion, stress redistribution interactions between fibres and matrix and the influence of inherent processing defects are all considered when describing the deformation and ultimate mechanical failure of these systems.